A study of the reliability of the fovea palatini for determining the posterior border of maxillary denture in filipinos - Atienza, Angelina A.
50 Filipino subjects were studied for the reliability of the fovea palatini in determining the posterior border of maxillary complete denture by direct measurement. The fovea was found to be an unreliable anatomical landmark.